PENERAPAN SANKSI PIDANA TERHADAP ANAK PELAKU TINDAK PIDANA - Krismiyarsi - (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
The type of crime that can be applied to the offender's offender is regulated in Article 71 of the Child Criminal Justice System Act, namely principal and additional criminal penalties. The principal crimes consist of criminal warnings, criminal conditions (coaching outside the institution, community service; or supervision), job training, coaching in institutions, and prisons. Additional penalties consist of: Deprivation of profits obtained from criminal acts or fulfillment of customary obligations . This is intended to provide an opportunity for the judge to choose which criminal is suitable for the child in the case he is handling. In practice, judges do not always impose criminal offenses similar to the types of criminal acts listed in the material criminal law in accordance with the article which are violated by the offender's offender, even the judge is not bound by the prosecutor's demands. The judge has the freedom to impose a criminal in accordance with his conscience. In addition to being influenced by juridical considerations, judges' decisions are also non-judicial considerations, namely the sociological, psychological, ethical, and historical aspects of the child.